A Springboard for physicians returning to practice. (20th December 2020) - Mullender, Claire; Gowland, Emily; Ford, Charlotte; Moore, Anna; Fisk, Marie; Bryant, Catherine; Le Ball, Karen; Deaner, Andrew; Birns, Jonathan
Abstract: Background: Many physicians take time out of training and have decreased confidence and poor performance ratings on their return. Courses employing multiple educational methods have been shown to be effective in easing learners into new clinical roles during transition periods but, to date, there is limited evidence for courses to support trainees returning to practice (RTP). Methods: A 2‐day course, named Springboard, was developed, specifically to address the needs of trainee physicians RTP. It employed a blended, multi‐modal approach to learning, including lectures, workshops, case‐based sessions, interactive panel discussions, small group teaching, peer‐led practical advice sessions and simulation training. Springboard was delivered eight times between 2014 and 2019 with a total of 540 doctors attending. We analysed participant pre‐and post‐course questionnaire feedback. Results: Reasons for doctors taking time out of training included parental leave, research, fellowships in education and leadership, health‐related absence and career breaks. Time out of training ranged between 3 months and 6 years. A significant pre/post‐course increase in candidates' self‐reported leadership skills and confidence in being prepared to return to practice was demonstrated alongside an appreciation of a multi‐modal, 'boot camp' course delivered by expert faculty and a networking experience. Discussion: Dedicated training courses tailored to the needs of physicians RTP provide an opportunity for improving confidence relating to many areas of clinical and non‐clinical practice as well as providing an environment for networking and sharing experiences. Further work would be valuable to establish the potential of providing this on a larger scale.